Influence of Extraperitoneal Metastases on the Curative-Intent Management of Colorectal Peritoneal Metastases - Schell, Frédéric; Kefleyesus, Amaniel; Benzerdjeb, Nazim; Passot, Guillaume; Rousset, Pascal; Omar, Alhadeedi; Villeneuve, Laurent; Péron, Julien; Glehen, Olivier; Kepenekian, Vahan (Annals of surgical oncology, 2023)
Background Selected patients with colorectal cancer peritoneal metastasis (CRPM) and extraperitoneal disease could be treated radically with a multimodal approach combining complete cytoreductive surgery, thermoablation, radiotherapy, and systemic and intraperitoneal chemotherapy. The impact of extraperitoneal metastatic sites (EPMS) in this setting remains unclear. Patients and Methods Patients with CRPM undergoing complete cytoreduction in 2005–2018 were grouped in: peritoneal disease only (PDO), one EPMS (1 + EPMS), two or more EPMS (2 + EPMS). A retrospective analysis compared overall survival (OS) and postoperative outcomes. Results Of 433 patients, 109 had 1 + EPMS and 31 had 2 + EPMS. Overall, 101 patients had liver metastasis, 19 lung metastasis, and 30 retroperitoneal lymph node (RLN) invasion. The median OS was 56.9 months. There was no significant OS difference between PDO and 1 + EPMS groups (64.6 and 57.9 months, respectively), whereas OS was lower in the 2 + EPMS group (29.4 months, p = 0.005). In multivariate analysis, 2 + EPMS [hazard ratio (HR) 2.86, 95% confidence interval (CI) 1.33–6.12, p = 0.007], Sugarbaker’s Peritoneal Carcinomatosis Index (PCI) > 15 (HR 3.86, 95% CI 2.04–7.32, p < 0.001), poorly differentiated tumors (HR 2.62, 95% CI 1.21–5.66, p = 0.015), and BRAF mutation (HR 2.10, 95% CI 1.11–3.99, p = 0.024) were independent poor prognostic factors, while adjuvant chemotherapy was beneficial (HR 0.33, 95% CI 0.20–0.56, p < 0.001). Patients with liver resection did not show higher severe complication rates. Conclusion In patients with CRPM selected for a radical surgical approach, limited extraperitoneal disease involving one site, notably the liver, does not seem to significantly impair postoperative results. RLN invasion appeared as a poor prognostic factor in this population.